Numerical Modeling of the Heating Phase of the Selective Laser Sintering Process - Siginer, D (Elsevier Masson SAS, 2017)
An accurate model and numerical method to simulate heat transfer for radiative heating of granular media is developed based on a modified Monte Carlo – ray tracing method and the Mie scattering theory. The effect of scattering on the radiative transfer and heat diffusion in semi-transparent polymer powder beds during laser sintering process is investigated via a 3D numerical model based on Discrete Elements Method (DEM) specifically developed for this purpose. In particular we show that DEM in combination with the specially developed Monte Carlo method is far more suitable to simulate radiative heat transfer and heat diffusion in a granular bed, polymeric or metallic, than the Finite Element Method (FEM). The method presented in this paper is particularly suitable for the simulation of additive manufacturing processes where similar radiative phenomena are of central importance. © 2017 Elsevier Masson SAS